"Second set of eyes:" Family caregivers and post-acute home health care during the COVID-19 pandemic. (April 2023) - Russell, David; Burgdorf, Julia G.; Washington, Karla T.; Schmitz, Jennifer; Bowles, Kathryn H.
Abstract: Objectives: This study aimed to explore how the COVID-19 pandemic shaped the experiences of family caregivers of older adults who were hospitalized with COVID-19 and discharged to post-acute, skilled home health care (HHC) services. Methods: Thirty semi-structured interviews with family caregivers of older adults who received services from a large, not-for-profit HHC agency following hospitalization with COVID-19 infection were conducted between March-July 2021 and analyzed using thematic analysis. Results: During the pandemic, family caregivers encountered societal and institutional barriers to assisting older adults across post-acute care transitions. These barriers included hospital visitation restrictions as well as difficulties accessing community-based resources and medical equipment. Despite limitations and delays in HHC services, many family caregivers identified post-acute HHC, delivered in-person or via telehealth, as important to addressing care gaps for older adults, as well as their own needs for training and support during the pandemic. Conclusions: Policies intended to reduce the spread of COVID-19 introduced new challenges for caregivers during HHC. However, HHC agencies and their staff adapted within this context to provide a needed bridge of support. Highlights: Caregivers experienced barriers to assisting with post-acute care during COVID. Hospital discharge and transfer policies reduced information/communication sharing. Post-acute home health care was important to addressing care gaps for older adults. Caregivers expressed the value of support from social workers and aides.